Systems biology to unravel Western diet-associated triggers in inflammatory bowel disease - Konjar, Špela; Benedik, Evgen; Šestan, Marko; Veldhoen, Marc; Županič, Anže (Frontiers in Immunology, 2025)
The global rise in inflammatory bowel disease (IBD) and other non-communicable diseases (NCDs) over the past five decades has coincided with the widespread adoption of a Western diet and lifestyle. These conditions, characterised by chronic inflammation, are shaped by complex interactions between genetic, environmental, immunological, and microbial factors. The Western diet rich in, refined sugars, unhealthy fats, ultra-processed foods and excess salt, is increasingly recognised as a major contributor to immune dysfunction, microbial dysbiosis, and compromised intestinal barrier integrity, all hallmarks of IBD. Systems biology offers a powerful framework for untangling the complexity of IBD by integrating large-scale biological data from various sources, leveraging computational modelling, high-throughput analyses, and network-based approaches to identify key regulatory pathways and molecular interactions driving disease progression. Complementary to this, nutritional epidemiology provides critical insights into the role of diet in IBD pathogenesis. By combining systems biology with nutritional epidemiology, researchers can move toward personalised dietary interventions and new therapeutic strategies, offering new opportunities for prevention and addressing the growing burden of IBD in societies adopting Western lifestyles. This review synthesise current findings and proposes integrated approaches for future precision prevention and treatment of IBD.